Digital Forensics Implementation on CCTV Using ISO/IEC 27037 and ISO/IEC 27042 - Zakaria Dwi Arman Maulana; Mukhlis Prasetyo Aji; Agung Purwo Wicaksono; Harjono (Jurnal E-Komtek, 2025)
Digital evidence in the form of CCTV footage is crucial data in legal investigations, but its integrity and authenticity are often questioned due to the lack of standardization of digital forensic procedures. This study aims to design and test the effectiveness of the implementation of a digital forensic framework based on the international standards ISO/IEC 27037:2012 (guidelines for acquisition and preservation) and ISO/IEC 27042 (guidelines for analysis and interpretation). The research method involves the application of the four-stage procedural ISO/IEC 27037 (Identification, Collection, Acquisition, and Preservation) on a CCTV V380 MicroSD card, followed by analysis using ISO/IEC 27042 principles and Autopsy software. The results show that this framework is fully effective. The integrity of the digital evidence is guaranteed, evidenced by the consistency of hash values ​​(MD5 and SHA1) that are verified Matched throughout the acquisition process until the preparation for analysis. Furthermore, the analysis procedure successfully retrieves information from videos that have been deleted from Unallocated Space, complete with important forensic metadata. This study concludes that the ISO/IEC framework has proven effective in ensuring the authenticity of evidence, and is therefore recommended as a scientifically and legally valid standard operating procedure model for forensic practitioners.